Karakteristik Pasien Hipertensi Pada Puskesmas Pertiwi Makassar - Musdalifah Eka Pratiwi; Mutmainnah Mutmainnah (Yayasan Citra Cendekia Celebes, 2021)
Hypertension is an increase in blood flow pressure that occurs in the human body which is one of the most common diseases found, according to the NHLBI (National Heart, Lung, and Blood Institute), 1 in 3 patients suffering from hypertension have risk factors for myocardial infarction, stroke, acute kidney failure and also death. The purpose of this study was to determine the description of the characteristics of hypertension patients in Pertiwi Makassar Health Center. This research was conducted on all patients diagnosed with hypertension at the Pertiwi Puskesmas in September 2019. The study was conducted with a descriptive study using an observational approach to see a description of the characteristics of hypertensive patients at the Pertiwi Puskesmas. These characteristics include age, sex and body mass index. From 134 people it can be seen that the number of male patients with hypertension is 55 people (41.04%) and the number of female patients with hypertension is 79 people (58.95%). The number of patients aged <40 years, amounting to 5 people (3.73%), the number of patients aged 40-45 years which amounted to 4 people (2.98%), the number of patients aged 46-50 years which amounted to 11 people (8.20 %), and the number of patients> 50 years old totaling 114 people (85.07%). The number of hypertensive patients who are underweight is 2 people (1.49%), the number of normal hypertension patients is 41 people (30.59%), the number of hypertensive patients who are overweight is 42 people (31.34%), the number of hypertensive patients who are Obese I is 48 people (35.82%) and the number of hypertensive patients who are Obesity II is 2 people (1.49%). Based on the results of the study it was found that women are more at risk of developing hypertension than men, aged> 50 years more than other ages and hypertensive patients are far more classified as obese I nutritional status.